Investigation of the effects of some demographic characteristics of female athletes on emotional intelligence and life satisfaction - YAMAN, ÇETİN (My University, 2024)
In many subjects and fields, emotional intelligence refers to the ability of individuals to understand, express and manage their own emotions and the emotions of others. Especially sport is known to have a significant effect on emotional intelligence. In this study, it was aimed to examine the effects of some demographic characteristics of female athletes on emotional intelligence and life satisfaction. The participants were all women and analyses were performed by taking into account age groups, sports branches and education departments. Emotional intelligence and life satisfaction scales were evaluated by factor analysis and the suitability of the data was confirmed by Bartlett\"s test. The internal consistency of the questionnaire was evaluated with Cronbach\"s alpha coefficients. Anova, Kruskal Wallis and Jonckheere-Terpstra tests were used to analyse the data. All analyses were performed with SPSS v22.0. 34% of the participants were 18-21 years old, 45% were 22-25 years old and 21% were over 26 years old. 31% were interested in team sports and 69% were interested in individual sports. The fields of education are 37% coaching, 32% physical education and sports teaching, 31% sports management. According to the factor analysis results, Bartlett\"s test p<0.001 and KMO coefficient 0.896 were found. Cronbach\"s alpha coefficients ranged between 0.583 and 0.924. While some factors differed according to age, no difference was found according to sport branch. While evaluation of own emotions and social skills differed according to departments, other factors did not differ. Participants over 26 years of age had low scores in the use of emotions and life satisfaction factors. These findings provide important clues for developing strategies for improving emotional intelligence and increasing life satisfaction.

En muchas materias y campos, la inteligencia emocional se refiere a la capacidad de las personas para comprender, expresar y gestionar sus propias emociones y las de los demás. Especialmente el deporte es conocido por tener un efecto significativo en la inteligencia emocional. En este estudio, se pretendía examinar los efectos de algunas características demográficas de las deportistas sobre la inteligencia emocional y la satisfacción vital. Las participantes fueron todas mujeres y los análisis se realizaron teniendo en cuenta los grupos de edad, las ramas deportivas y los departamentos educativos. Las escalas de inteligencia emocional y satisfacción vital se evaluaron mediante análisis factorial y la idoneidad de los datos se confirmó mediante la prueba de Bartlett. La consistencia interna del cuestionario se evaluó con los coeficientes alfa de Cronbach. Para analizar los datos se utilizaron las pruebas de Anova, Kruskal Wallis y Jonckheere-Terpstra. Todos los análisis se realizaron con SPSS v22.0. El 34% de los participantes tenía entre 18 y 21 años, el 45% entre 22 y 25 años y el 21% tenía más de 26 años. El 31% estaban interesados en deportes de equipo y el 69% en deportes individuales. El 37% eran entrenadores, el 32% profesores de educación física y deportes y el 31% gestores deportivos. De acuerdo con los resultados del análisis factorial, se encontraron la prueba de Bartlett p<0,001 y el coeficiente KMO 0,896. Los coeficientes alfa de Cronbach oscilaron entre 0,583 y 0,924. Mientras que algunos factores diferían en función de la edad, no se encontraron diferencias en función de la rama deportiva. Mientras que la evaluación de las propias emociones y las habilidades sociales diferían según los departamentos, otros factores no diferían. Los participantes mayores de 26 años obtuvieron puntuaciones bajas en los factores de uso de las emociones y satisfacción vital. Estos resultados proporcionan pistas importantes para desarrollar estrategias que mejoren la inteligencia emocional y aumenten la satisfacción vital. Palabras clave: inteligencia emocional; satisfacción vital; deporte; mujer; atleta.
Investigación de los efectos de algunas características demográficas de las deportistas sobre la inteligencia emocional y la satisfacción vital
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Rehabilitasyon; Clinical Medicine (Med); Clinical Medicine; Rehabilitation; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; athlete; emotional intelligence; life satisfaction; sports; woman; inteligencia emocional; satisfacción vital; deporte; mujer